(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article discusses the main content from the point of view of science, corrosion processes in civil engineering represent the most real threat to metal structures. Regardless of the thickness of the steel, rust quickly renders the material unusable, the technology of protection against the appearance and development of corrosion requires an increase in the corrosion resistance of structures.